Berkarya Untuk Desa, Peduli Lingkungan Bersama Kita Cegah Dan Akhiri Penyebaran Wabah Covid-19 Di Desa Uwemanje Kecamatan Kinovaro Kabupaten Sigi - Daniel T Todapa; Juemi Juemi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
The community service activity entitled "Working for the Village, Caring for the Environment Together We Prevent and End the Spread of Covid 19" was carried out in Uwemanje Village, Kinovaro District, Sigi Regency. The aim of this community service activity is to assist the village government in encouraging the community to think creatively in entrepreneurship while protecting the surrounding natural environment from being damaged and continuing to implement health protocols so as to reduce the effects of the pandemic, namely the decline in the community's economy. Through this activity, the people of Uwemanje Village understand the importance of creativity and village government participation in entrepreneurial competition. The targets of the activity are residents, traders and the Uwemanje village government. The expected output from this service activity is that the Uwemanje Village government in particular, and Sigi Regency in general, can empower residents to protect the surrounding environment and participate in competing in the digital-based business world.